Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. Smart leadership as an entry point to achieving competitive advantage in the Al-Kharj Governorate Education DepartmentMrs. Munirah Abdullah Al-Masoud , Dr. Zainab Awwad Mofleh Darwish2. The Obstacles of Implementing Blended Learning Teaching from the Perspectives of Intellectual Disabilities Teachers in JeddahMrs. Seham Hamadi Al-Sulami, Dr. Lama Abdul Hakeem Sahab3. The Impact of the Variation of Digital Story's Presentation Patterns (static graphics\ animations) in Problem-Solving Based Learning on Developing Computer Skills for Middle-School Female StudentsMrs. Imtinan Mohammed Alzughaibi ,Prof. Mohammed Ibrahim Alshuwaie4. Attitudes of Human Resources in the Department of Education in Al-Kharj Governorate Towards Blended TrainingMrs. Noura Sultan Al-Dossary, Prof. Ajlan Mohammad Al-Shehri5. Reasons for the low achievement in mathematics among students of the first three grades of the basic education stage from the viewpoint of teachers and educational supervisors in Benghazi city - LibyaLecturer \ Fatma Naser Ali Mohamed, Dr. Bothaina Fadil Bukhatwa , Mrs. Haajer Ayad Mohamed Alagelee6. Cognitive Bias and Its Relationship to the Level of Information Processing among Umm Al-Qura University Female StudentsMrs. Ehklas Ahmed Alharbi, Prof. Newar Mohammed Saad Alharbi7. Rationing the Test of Mathematic Ability (TOMA3.) on high classes primary school students (boys) at Gunfudah Educational DirectorateMr. Khader Mohammed Al-Zailay
Keywords: Journal of Educational and Psychological Sciences